2021
DOI: 10.1038/s41598-021-95475-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and magnetic response of poly(p-xylylene)–MnSb and MnSb films deposited at cryogenic temperature

Abstract: In this study, we employed several experimental techniques to investigate structure and magnetic properties of poly(p-xylylene)–MnSb composites synthesized by low-temperature vapor deposition polymerization technique and MnSb films deposited at various temperatures. The presence of MnSb nanocrystallites in the studied films was verified by the results of X-ray diffraction, electron microscopy and Raman spectroscopy studies. The obtained data revealed the formation of Sb-rich sublayer with well-oriented Sb grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…This drop-off in magnetization for the 65 nm Mn 1+δ Sb nanoparticles is consistent with the presence of excess interstitial Mn, which results in antiferromagnetic Mn–Mn electronic coupling along the c -axis due to a reduced c / a ratio and also in anti-parallel-aligned spins of non-coupled Mn atoms. , Notably, the M ( H ) curve of Mn 1+δ Sb nanoparticles at 2.5 K does not saturate at 50 kOe, instead showing a paramagnetic response when H exceeds approximately 10 kOe (Figure S16). Conflicting reference values for the M s of bulk MnSb are given in the literature; however, a commonly-accepted value is ∼700 emu/cc (98 emu/g), with the largest value observed experimentally being 772 emu/cc (107 emu/g) . Hence, at 2.5 K the 42 nm MnSb nanoparticles produced here show M s approaching that of the bulk material.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…This drop-off in magnetization for the 65 nm Mn 1+δ Sb nanoparticles is consistent with the presence of excess interstitial Mn, which results in antiferromagnetic Mn–Mn electronic coupling along the c -axis due to a reduced c / a ratio and also in anti-parallel-aligned spins of non-coupled Mn atoms. , Notably, the M ( H ) curve of Mn 1+δ Sb nanoparticles at 2.5 K does not saturate at 50 kOe, instead showing a paramagnetic response when H exceeds approximately 10 kOe (Figure S16). Conflicting reference values for the M s of bulk MnSb are given in the literature; however, a commonly-accepted value is ∼700 emu/cc (98 emu/g), with the largest value observed experimentally being 772 emu/cc (107 emu/g) . Hence, at 2.5 K the 42 nm MnSb nanoparticles produced here show M s approaching that of the bulk material.…”
Section: Resultsmentioning
confidence: 58%
“…91,93 Notably, the M(H) curve of Mn 1+δ Sb nanoparticles at 2.5 K does not saturate at 50 kOe, instead showing a paramagnetic response when H exceeds approximately 10 kOe (Figure S16). Conflicting reference values for the M s of bulk MnSb are given in the literature; however, a commonly-accepted value is ∼700 emu/cc (98 emu/g), 94 with the largest value observed experimentally being 772 emu/cc (107 emu/g). 57 Hence, at 2.5 K the 42 nm MnSb nanoparticles produced here show M s approaching that of the bulk material.…”
Section: ■ Introductionmentioning
confidence: 91%
“…The VDP apparatus employed in this study has been previously described. The initial precursor, the cyclic dimer of p -xylylene (Parylene N, Specialty Coating Systems, USA), was sublimated in a vacuum (10 –5 –10 –6 Torr) at 50 °C. Subsequently, at 650 °C in the pyrolysis zone, each precursor molecule was split into two p -xylylene monomer molecules.…”
Section: Methodsmentioning
confidence: 99%
“…21) Furthermore, a different research team recently reported their findings on the structural description and magnetic response of MnSb films deposited at cryogenic temperatures. 22) In parallel, other researchers have investigated the crystallographic orientation of primary and eutectic phases in a hypoeutectic Mn-Sb alloy. 23) To the best of our knowledge, no report exists on the temperature-dependent epitaxial growth of MnSb on GaAs (111) B substrates using MBE with wide-range characterization.…”
Section: Introductionmentioning
confidence: 99%